Inflammatory Myo-Fibroblastic Tumor of the Gallbladder with Multivisceral Involvement: Successful Treatment with Radical Surgery - Kwanchanok Losuwarat; Vor Luvira; Vasin Thanasukarn; Theerawee Tipwaratorn; Piti Ungarreevittaya (Case Reports in Hepatology)
Inflammatory myo-fibroblastic tumor (IMT) of the gallbladder is an extremely rare condition. Only seven cases have been reported. All of these were presented either with polyp/mass inside the gallbladder or gallbladder wall thickening, involving just one adjacent organ. We herein present a case of IMT of gallbladder presenting with a huge mass replacing the gallbladder with multiple organ involvement, successfully treated by en bloc multivisceral resection. Moreover, we have compared it with the characteristics of all reported cases of IMT of the gallbladder.